Identification of snake venom allergens by two-dimensional electrophoresis followed by immunoblotting. (January 2017) - Hu, Yujing; Yang, Liming; Yang, Haiwei; He, Shaoheng; Wei, Ji-Fu
Abstract: This allergic reaction to snake venom was described to occur in patients after recurrent exposure through bites in amateur and professional snake handlers, which might be underestimated and contribute to fatal snakebites in victim, independently from the toxicity of the venom itself. Few allergens were identified from snake venoms by normal SDS-PAGE, which cannot separate the snake venom completely. In the present study, we identified nine potential allergens by two-dimensional (2D) electrophoresis followed by immunoblotting (named as allergenomics) in Protobothrops mucrosquamatus venom. By multidimensional liquid chromatography-ion trap mass spectrometry (MDLC-ESI-LTQ-MS/MS) analysis, six allergens showed sequence similarity to snake venom serine proteinases. Other allergens showed sequence similarity to snake venom metalloproteinase. These allergic reactions to snake venom allergens might contribute to fatal snakebites in victim, independently. Highlights: Nine potential allergens were identified by 2D-PAGE followed by immunoblotting in Protobothrops mucrosquamatus venom. These allergens showed sequence similarity to snake venom serine proteinases and metalloproteinase. These allergic reactions to snake venom allergens might contribute to fatal snakebites in victim, independently.